Simple tools and techniques for enterprise risk management - Chapman, Robert J. (Wiley finance series, 2011)
Your business reputation can take years to build—and mere minutes to destroy The range of business threats is evolving rapidly but your organization can thrive and gain a competitive advantage with your business vision for enterprise risk management. Trends affecting markets—events in the global financial markets, changing technologies, environmental priorities, dependency on intellectual property—all underline how important it is to keep up to speed on the latest financial risk management practices and procedures. This popular book on enterprise risk management has been expanded and updated to include new themes and current trends for today's risk practitioner. It features up-to-date materials on new threats, lessons from the recent financial crisis, and how businesses need to protect themselves in terms of business interruption, security, project and reputational risk management. Project risk management is now a mature discipline with an international standard for its implementation. This book reinforces that project risk management needs to be systematic, but also that it must be embedded to become part of an organization's DNA. This book promotes techniques that will help you implement a methodical and broad approach to risk management. * The author is a well-known expert and boasts a wealth of experience in project and enterprise risk management * Easy-to-navigate structure breaks down the risk management process into stages to aid implementation * Examines the external influences that bring sources of business risk that are beyond your control * Provides a handy chapter with tips for commissioning consultants for business risk management services It is a business imperative to have a clear vision for risk management. Simple Tools and Techniques for Enterprise Risk Management, Second Edition shows you the way.